Highlife and taarab ‘revisited’ - Coester, M. (My University, 2016)
In this presentation I will talk about my roughly 10-years of Highlife research – Highlife in a trilocal and transnational perspective (that led to my habilitation thesis at the University of Bayreuth) - and then draw a comparative line to (the history) of popular music in East Africa, the so called Taarab music of the Swahili Coast, that can also be revisited as a modern, cross-boundary cultural formation of popular music.
Seminar
Keywords: Highlife research; transnational perspective; popular music; Africa